Highly Conducting Nanographite-Filled Paper Fabricated via Standard Papermaking Techniques - Isacsson, Patrik (ACS Appl Mater Interfaces, 2020)
[Image: see text] Eco-friendly and cost-effective materials and processes to manufacture functional substrates are crucial to further advance the area of printed electronics. One potential key component in the printed electronics platform is an electrically functionalized paper, produced by simply mixing common cellulosic pulp fibers with high-performance electroactive materials. Herein, an electronic paper including nanographite has been prepared using a standardized and scalable papermaking technique. No retention aid was needed to achieve a conducting nanographite loading as high as 50 wt %. The spontaneous retention that provides the integrity and stability of the nanographite paper, likely originates partially from an observed water-stable adhesion of nanographite flakes onto the fiber surfaces. The resulting paper exhibits excellent electrical characteristics, such as an in-plane conductivity of 107 S/cm and an areal capacitance of 9.2 mF/cm(2), and was explored as the back-electrode in printed electrochromic displays.